Toxicological Analysis of Ricin in Medicinal Castor Oil with Evaluation of Health Hazards - Riaz, S.; Farrukh*, M.A. (Asian Journal of Chemistry, 2014)
Ricin is a highly toxic, naturally occurring protein in castor bean plant and used as potential bio and chemical warfare agent, through which people can easily be affected by its all routes of exposure. Sixteen different medicinal castor oil samples were checked for contamination with ricin toxin. The classical and gel filtration methods for extraction of purified ricin were adopted. Confirmation of ricin was carried out by gel electrophoresis (SDS-PAGE). FTIR analysis was performed for specific ricin structure determination. Quantification of ricin present in castor oil samples was carried out by observing absorption at 279 nm on UV-visible spectrophotometer. The maximum amount of ricin found in medicinal castor oil samples is 0.713 mol L-1 (0.43 mg/10 mL). The possibility of finding ricin in castor oil may be correlated with adverse effects of medicinal castor oil intake. Minimum inhibition concentration of ricin was inferred against E. coli and Staphylococcus bacterial strains, by agar dilution method. While no effect of ricin was found on Staphylococcus strain.